Une gouvernementalité culturelle pour les prochaines générations ? L’évolution de la littérature pour enfants en Croatie lors des conflits de dissolution yougoslaves (1991-1995) - Léon de Perrot (Strenae)
The present article tackles the way the competitive authoritarian regime of the Croatian Democratic Community (HDZ) sought, in the early years of Croatia’s independent and the ensuing war on its territory, to provide an antagonistic and nationally-exclusivist framework of understanding of the world to its younger population – the next generation. The article thus questions both the building of control over the publishing sector and the ensuing production of narratives in children’s literature through the concept of “cultural governmentality”.